2012
DOI: 10.1111/j.1464-410x.2012.11480.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose rate brachytherapy compared with open radical prostatectomy for the treatment of high‐risk prostate cancer: 10 year biochemical freedom from relapse

Abstract: Objective• To compare long-term biochemical control of high-risk prostate cancer in those men receiving high-dose rate brachytherapy (HDRB) and radical prostatectomy (RP). Patients and methods• The 10-year biochemical freedom from relapse (BFR) was calculated for 243 patients who underwent either RP or combined therapy with HDRB + external beam radiotherapy + androgen deprivation between 1998 and 2000.• Inclusion criteria: clinical stage ≥ T2b, or Gleason sum ≥ 8, or PSA level of > 20 ng/ mL. Groups were appra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…All the men included in the present cohort received only 6 months of neoadjuvant ADT, with the exception of 11 men after 2006 who had multiple high‐risk prostate cancer features who also received adjuvant ADT for 12–24 months. The role of ADT in intermediate‐risk prostate cancer remains controversial, especially in cases of favorable, low volume intermediate‐risk prostate cancer . Men with intermediate risk factors in the present series had excellent bNED rates during the follow‐up period.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…All the men included in the present cohort received only 6 months of neoadjuvant ADT, with the exception of 11 men after 2006 who had multiple high‐risk prostate cancer features who also received adjuvant ADT for 12–24 months. The role of ADT in intermediate‐risk prostate cancer remains controversial, especially in cases of favorable, low volume intermediate‐risk prostate cancer . Men with intermediate risk factors in the present series had excellent bNED rates during the follow‐up period.…”
Section: Discussionmentioning
confidence: 60%
“…It is unlikely that a randomized trial comparing these two treatments will be performed. A non‐randomized comparison of biochemical recurrence by Savdie et al showed outcomes for men in the high‐risk cohort undergoing radical prostatectomy were as predicted by the pre‐treatment nomogram, whereas outcomes for the men undergoing HDR brachytherapy were significantly better than was predicted by the Kattan surgical nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 There are retrospective Australian data supporting the hypothesis that dose escalation using HDRB boost results in improved biochemical disease control compared with EBRT [17][18][19] or RP for men with high-risk disease. 20 Various factors, such as cost, radiation protection, technical expertise and advances in EBRT delivery, have limited the implementation of prostate HDRB to a relatively small number of specialist centres.…”
Section: Radiation Dose and Mode Of Deliverymentioning
confidence: 99%
“…Limited long-term follow-up exclusively in the contemporary prostate-specific antigen (PSA) era is also restricted to laparoscopy or open approaches. Only five cohorts [7][8][9][10][11] have published 10-yr biochemical recurrence (BCR), three for open prostatectomy [7][8][9] that report BCRFS rates ranging between 39% and 93%, depending on factors such as stage, Gleason score, or surgical margins, and two for laparoscopy [10,11] that document overall BCRFS rates of 76% and 71%, respectively.…”
mentioning
confidence: 99%